(untitled) (Journal of Philosophy, Culture and Political Science, 2019)
The celsius article analyzes the phenomenon of the cultural values of the Kyzylorda region in the context of the phenomenon of the phenomenon, which is related to the differentiated values of social phenomena investigated. There are also analyzed the results and presented the critical assessment of ethnicity in the ethno-social space. In the context of the context of social phenomena in the field of cultural self-efficacy, the region has a great deal of importance in the field of science, focusing on the emphasis on the excellence, as well as predetermined predictors of social and philosophical methodology. The authors analyse modern aspects of methodological approaches to the study of culture values. In the article authors consider essence in the formation of culture values. The original cultural values in the Syr-Darya region have a unique cultural and anthropological analysis of their potential trends in social-cultural models in ethnicity self-actualization in modern Kazakhstan. Key words: National Identity, value, survey, tolerance, students, culture.